Effects of local heat on metabolic health, frailty risk, and exercise adaptations in pre-diabetic older adults: Protocol for the Heat and Exercise in Aging as Therapy (HEAT) clinical trial - Hui-Ying Luk; Casey R. Appell; Fangyuan Zhang; Jarrod Blinch; K. Sreekumaran Nair; Chwan-Li Shen; Danielle E. Levitt (PLoS ONE, 2026)
Introduction Glycemic dysregulation is a hallmark of type 2 diabetes (T2D) and contributes to skeletal muscle (SKM) loss and frailty risk, especially in older adults. Glycemic control and physical function are supported by SKM capillarization and mitochondrial function, and their impairment contributes to T2D development. While high-intensity interval training (HIIT) is a promising intervention, adherence and effectiveness remain concerns for prescribing HIIT among older adults at risk for T2D. Local heat therapy (LHT) may be a more practical initial strategy to improve SKM architectural factors and precondition SKM, enhancing physiological adaptations to exercise in this population. Methods and analysis Heat and Exercise in Aging as Therapy (HEAT) is a two-phase, randomized, sham-controlled clinical trial investigating the efficacy of LHT to improve glycemic control and decrease frailty risk via improved SKM architecture among older adults with prediabetes. LHT is tested as a standalone intervention and as a means to precondition SKM for subsequent HIIT, improving exercise adaptations. In Phase 1, LHT and sham (CON) groups apply heat pads for 90 minutes/day, 6 days/week, for 12 weeks. A separate HIIT group completes 4x4-minute cycling intervals at 90–95% VO₂peak, 3 days/week. In Phase 2, LHT and CON groups begin HIIT. Participants (≥50 years) have impaired fasting glucose (100–125 mg/dL) and/or HbA1c (5.7–6.4%). Biospecimen collection and clinical assessments occur at baseline (T1), after Phase 1 (T2), and Phase 2 (T3). To our knowledge, this is the first study to determine the use of local heat pad on pre-diabetic older population. If successful, LHT may be a practical, scalable, non-invasive intervention to improve glycemic control and reduce frailty risk in older adults with prediabetes, preventing progression to T2D.